ACUPUNCTURE FOR PAIN CONTROL AMONG BREAST CANCER PATIENTS: AN INTEGRATIVE LITERATURE REVIEW - Cavalheiro, Andréia dos Reis; dos Santos, Juliano (Seven Editora, 2025)
Introduction: Pain is a frequent symptom among women with breast cancer and acupuncture is a widely used intervention to control the symptoms of the disease and minimize the impact of the adverse effects of cancer treatment. However, the contexts of use and their effectiveness need to be better explored. Objective: To describe the studies that used acupuncture as an intervention for pain control in patients with breast cancer. Method: Integrative literature review. The searches were carried out using the descriptors breast cancer, pain, and acupuncture in the Scientific Electronic Library (SCIELO), National Library of Medicine (PubMed) and Latin American and Caribbean Literature on Health Sciences (LILACS) databases through the Virtual Health Library (VHL) and in the Cumulative Index to Nursing and Allied Health Literature (CINAHL).  SCOPUS and Web of Science. To report the integrative review and systematize the inclusion process, the criteria of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses were used. Results: The final sample consisted of 17 studies, grouped into four thematic categories: arthralgia related to aromatase inhibitors (41.2%; n=7); multiple symptoms/complications related to treatment (29.4%; n=5); pain and chronic pain (17.6%; n=3) and (11.8%; n=2) peripheral neuropathy and chemotherapy. The studies were mostly published by Asian countries (64.7%; n=11), mainly in the years 2020 (29.4%) and (23.5%) 2021, by journals related to oncology and complementary/integrative practices. Systematic reviews with meta-analysis accounted for the majority of studies (52.9%; n=9), followed by Randomized Clinical Trials (n=3) and (n=2) pilot studies. Among the instruments for assessing pain, the BPI stood out, used in 70.6%; n=12) of the cases. Most studies (52.9%) used systemic acupuncture alone, 29.4% used systemic acupuncture and auriculotherapy, and two studies (11.8%) used systemic acupuncture and acupressure. In most studies (76.5%; n=13), acupuncture decreased pain (intensity and/or impact and/or mean pain) among women with breast cancer. Conclusion: Although there is no consensus, in most studies, acupuncture decreased pain (intensity and/or impact and/or mean pain and/or worse pain) among patients with breast cancer.DOI: https://doi.org/10.56238/sevened2024.037-205